Mesoporous goethite for rapid and high-capacity fluoride removal from drinking water. Issue 4 (August 2021) - Zhao, Xiao; Li, Ying; Carroll, Kenneth C.; Li, Fangfang; Qiu, Liuchao; Huo, Zailin
Abstract: Fluoride (F) contamination is widely distributed due to natural or anthropogenic causes. A series of mesoporous goethite (α-FeOOH) were synthesized by hydrothermal treatment for rapid F removal from water. The morphology of adsorbents was found to be controlled by varying the hydrothermal and calcination conditions. A highly crystallized FeOOH can be prepared at hydrothermal temperature of 80 °C without further calcination. The sorption isotherm data could be adequately described by Freundlich model and kinetic data followed pseudo-second-order kinetic model. The highest adsorption capacity is as high as 80.1 mg/g. Mesoporous FeOOH exhibited high adsorption capacity in a wide pH range of 3–10 with final pH falling into a stable range (pH 5–6). The presence of Cl - and NO3 - seldom impacted the adsorption performance, while addition of high concentrations of CO3 2- and PO4 3- (30 mg/L) weakened the adsorption capacity up to 18.2%. For the recycle tests with real F-contaminated groundwater, the removal efficiency dropped slightly from 93.1% (at cycle 1) to 91.8% (at cycle 5), suggesting the adsorbents is powerful for practical use. The FTIR, SEM, and XPS characterization results all confirmed the adsorption of F and revealed that the major adsorption mechanism is the ion-exchange between F ions and hydroxyl groups on the surface of FeOOH. Graphical Abstract: ga1 Highlights: Mesoporous goethite (α-FeOOH) was synthesized by hydrothermal treatment. Mesoporous FeOOH exhibited high adsorption capacity in a wide pH range. Ion-exchange between F ions and hydroxyl groups on the surface of FeOOH is the major adsorption mechanism.